Impact of the 2017 American Academy of Pediatrics Guideline on Hypertension Prevalence Compared With the Fourth Report in an International Cohort. Issue 6 (December 2019) - Yang, Liu; Kelishadi, Roya; Hong, Young Mi; Khadilkar, Anuradha; Nawarycz, Tadeusz; Krzywińska-Wiewiorowska, Małgorzata; Aounallah-Skhiri, Hajer; Motlagh, Mohammad Esmaeil; Kim, Hae Soon; Khadilkar, Vaman; Krzyżaniak, Alicja; Ben Romdhane, Habiba; et al.
Abstract : In 2017, the American Academy of Pediatrics (AAP) updated the clinical practice guideline for high blood pressure (BP) in the pediatric population. In this study, we compared the difference in prevalence of elevated and hypertensive BP values defined by the 2017 AAP guideline and the 2004 Fourth Report and estimated the cardiovascular risk associated with the reclassification of BP status defined by the AAP guideline. A total of 47 200 children and adolescents aged 6 to 17 years from 6 countries (China, India, Iran, Korea, Poland, and Tunisia) were included in this study. Elevated BP and hypertension were defined according to 2 guidelines. In addition, 1606 children from China, Iran, and Korea who were reclassified upward by the AAP guideline compared with the Fourth Report and for whom laboratory data were available were 1:1 matched with children from the same countries who were normotensive by both guidelines. Compared with the Fourth Report, the prevalence of elevated BP defined by the AAP guideline was lower (14.9% versus 8.6%), whereas the prevalence of stages 1 and 2 hypertension was higher (stage 1, 6.6% versus 14.5%; stage 2, 0.4% versus 1.7%). Additionally, comparison of laboratory data in the case-control study showed that children who were reclassified upward were more likely to have adverse lipid profiles and high fasting blood glucose compared with normotensive children. In conclusion, the prevalence of elevated BP and hypertension varied significantly between both guidelines. Applying the new AAP guideline could identify more children with hypertension who are at increased cardiovascular risk. Abstract : Supplemental Digital Content is available in the text.